Elimination of mother-to-child transmission of HIV and Syphilis (EMTCT): Process, progress, and program integration - Taylor, Melanie (PLoS Med, 2017)
Melanie Taylor and colleagues discuss progress towards eliminating vertical transmission of HIV and syphilis.